Identifying Components and Examining Causal Relationships of Optimal Budgeting in Iran's Education System - Basami , Reza; Borzoian Shirvan , Samad; Fatemi , Adel (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective:  The objective of this study is to identify the components and examine the causal relationships of optimal budgeting in Iran's education system.Methodology: This research employed an applied and exploratory approach, utilizing descriptive and survey methods for data collection. Initially, the components and sub-components of optimal budgeting were identified through a review of literature, including theses, articles, and books. A designed questionnaire was then reviewed and completed by experts and specialists in the field of industrial management and academic professors using the fuzzy Delphi method. Subsequently, the causal relationships between the components were determined using DEMATEL multi-criteria decision-making methods.Findings: The study identified three main components—Ability (ABI), Authority (AUT), and Acceptance (ACC)—as crucial for optimal budgeting in Iran's education system. The results from the Delphi fuzzy method indicated a consensus among experts, with all components having definitive means above 0.4. The DEMATEL analysis revealed that the Authority (AUT) component has the highest influence and lowest receptivity among the components, making it the most significant factor. It was found that enhancing the Authority (AUT) component can positively influence the other components, leading to improved budgeting outcomes.Conclusion: For optimal budgeting in Iran's education system, controlling the main components—Ability (ABI), Authority (AUT), and Acceptance (ACC)—is essential. Enhancing the Authority (AUT) component can lead to better control of other components, resulting in improved budgeting with reduced costs and time. Systemic budgeting is crucial for the growth and development of countries, and it is imperative for Iran's General Directorate of Education to adopt this strategy to align with global trends.